Development of A Bima Local History Module Based on Study Tours in Local Course Learning for High School Students - Syahbuddin Syahbuddin; Tati Haryati; A. Gafar Hidayat (JURNAL PENDIDIKAN IPS, 2025)
Local content learning in schools does not adequately showcase insights into historical artifacts. Therefore, it is necessary to develop a local history module with a study tour/field trip design, so that students not only understand the material but also visit places with historical artifacts in Bima. The objectives of this research are: 1) to describe the stages of developing a study tour-based Bima local history module; 2) to test the feasibility and practicality of the study tour-based Bima local history module in local content learning. The method used is the research and development (R&D) 4 D Model, namely: Define, Design, Develop, and Disseminate. Based on the results of the research, the average score obtained from the validator is 80.5%, with a very valid/feasible category. Covering material, learning presentation, language, design appearance. Furthermore, in terms of practicality, an average value of 80.6% was obtained. Thus, the module is easy for teachers and students to use. In addition, it provides guidance on the implementation of study tours, so that students can be directly involved in study tour activities. However, the problem of direct visit times to local historical objects is less supportive when learning takes place; for this reason, this module is equipped with virtual images that represent local historical artifacts.